MUAC and Hemoglobin Among Adolescent Girls: Implications For Community-Based Nutritional Interventions - Nancy Swanida Henriette Malonda; Yulianty Sanggelorang; Alpinia Shinta Pondagitan; Syefira Salsabila (YCAB Publisher, 2026)
Background: Anemia among adolescent girls is a global public health issue that can impair growth, cognitive function, and future reproductive health. Objectives: This study aimed to analyze the influence of various nutritional, socioeconomic, and physiological factors on hemoglobin levels among adolescent girls. Methods: A cross-sectional study was conducted involving 50 adolescent girls aged 11–19 years. Data collection included anthropometric measurements, dietary intake assessments, and a structured questionnaire on sociodemographic characteristics and menstrual patterns. Hemoglobin levels were measured using a standard hemoglobinometer. Bivariate analysis using Spearman’s Rho and multivariate analysis using multiple linear regression were performed to determine the associated factors. Results: The prevalence of anemia was 26%. Bivariate analysis showed significant correlations between hemoglobin levels and mid-upper arm circumference (r = 0.356; p = 0.011), protein intake (r = 0,271; p = 0.050), and iron intake (r = 0.293; p = 0.039). Multivariate analysis revealed that MUAC and protein intake were the most influential factor affecting hemoglobin levels (p = 0.021 and 0.025 respectively). Other variables such as BMI-based nutritional status, parental income, vitamin C intake, anemia-related knowledge, and menstrual characteristics did not show significant associations. Conclusion: The findings highlight that improving dietary intake particularly of protein and iron and regularly monitoring MUAC are practical steps to reduce anemia among adolescent girls. These insights offer valuable guidance for nutritional interventions focused on adolescent well-being. Keywords: adolescent girls; hemoglobin; mid-upper arm circumference; protein intake; iron intake; nutritional status